2020
DOI: 10.1111/mpp.12985
|View full text |Cite
|
Sign up to set email alerts
|

Flippases play specific but distinct roles in the development, pathogenicity, and secondary metabolism of Fusarium graminearum

Abstract: The membrane trafficking system is important for compartmentalization of the biosynthesis pathway and secretion of deoxynivalenol (DON) mycotoxin (a virulence factor) in Fusarium graminearum. Flippases are transmembrane lipid transporters and mediate a number of essential physiological steps of membrane trafficking, including vesicle budding, charging, and protein diffusion within the membrane. However, the roles of flippases in secondary metabolism remain unknown in filamentous fungi. Herein, we identified fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 60 publications
(122 reference statements)
0
19
0
Order By: Relevance
“…Among the six AgNP-induced FgTRI genes, FgTRI1 encodes a calonectrin oxygenase FgTri1, which catalyzes the late step in DON biosynthesis and is delivered to the toxisome under DON induction conditions. Therefore, the formation of toxisomes can be reflected by FgTri1, which shows a positive correlation with DON production [42] . To characterize the subcellular localization of FgTri1 under AgNP treatment, FgTRI1-GFP was introduced into the FgTri1 mutant ΔFgTri1 to obtain FgTri1-GFP expressing strain (ΔFgTri1::FgTri1-GFP) for the toxisome induction assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the six AgNP-induced FgTRI genes, FgTRI1 encodes a calonectrin oxygenase FgTri1, which catalyzes the late step in DON biosynthesis and is delivered to the toxisome under DON induction conditions. Therefore, the formation of toxisomes can be reflected by FgTri1, which shows a positive correlation with DON production [42] . To characterize the subcellular localization of FgTri1 under AgNP treatment, FgTRI1-GFP was introduced into the FgTri1 mutant ΔFgTri1 to obtain FgTri1-GFP expressing strain (ΔFgTri1::FgTri1-GFP) for the toxisome induction assay.…”
Section: Resultsmentioning
confidence: 99%
“…DON is the primary mycotoxin produced by F. graminearum during pathogenesis, and its biosynthesis is regulated by 15 trichothecene biosynthesis genes ( FgTRI s) [42] . Owing to the threat of DON to human and animal health, the control efficiency of DON contamination is considered a critical indicator to evaluate and apply fungicides for the management of FHB [43] .…”
Section: Resultsmentioning
confidence: 99%
“…Also, double gene deletion of DNFA and DNFB or DNFC and DNFD is lethal, indicating that flippases also play a different role in the vegetative growth in A. nidulans ( Schultzhaus et al, 2015 , 2019 ). In the plant pathogenic fungi F. graminearum , except for FgDNFA , the other flippases, including FgDNFB (homolog of DRS2 ), are not critical for vegetative growth ( Yun et al, 2020 ). Similarly, the loss of two flippase genes MgPDE1 , and MgAPT2 (homolog gene of DRS2 ), had no adverse influence on the vegetative growth of M. grisea.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that AnDnfA and AnDnfB play a pivotal role in the asymmetric distribution of phosphatidylserine in the phytopathogenic fungus A. nidulans ( Schultzhaus et al, 2015 ). Recently, Yun et al (2020) found that FgDnfB and FgDnfD are involved in the transport of phosphatidylcholine. Our findings showed that P4 ATPase PcApt1 specifically transports PS rather than PE and PC in P. capsici .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation